Rice Marketing Strategy through E-Commerce as an Effort to Improve Farmers' Welfare: A Case Study of Rice Farmers in Serdang Bedagai Regency. Rice Farmers in Serdang Bedagai Regency - Rachmawati, Yeni; Flora Silalahi; Fahra Az-zahra (SEAN Institute, 2024)
This study analyzes internal and external factors that can affect agricultural businesses in Melati 2 Hamlet using the SWOT analysis method supported by the IFAS and EFAS matrices. Based on the results of the study, it was found that farmers in Melati 2 Hamlet have very good internal strengths, indicated by the existence of well-coordinated farmer groups, long experience of farmers and the readiness and willingness of farmers to make marketing innovations. The IFAS score of 3.70 indicates that the internal strengths of farmers are very strong so that they can overcome the weaknesses that farmers have in the form of limited equipment and capital. The EFAS score of 3.55 indicates that there are great opportunities that can be utilized such as technological advances and easy internet access. Strategic recommendations from the results of the SWOT analysis using the IFAS and EFAS matrices are the use of technology and e-commerce, collaboration with agricultural extension workers and optimization of administrative processes. The existence of the right strategy is expected to improve the welfare of farmers in Melati 2 Hamlet, Perbaungan Sub-District, Serdang Bedagai Regency.